(untitled) (Global Journal of Human-Social Science, 2014)
Introduction-For the past one thousand years militant Islam has been battling West European civilization or imperialism. Today, pax Americana, the forebear of pax Britannica (American and British peace) have continued with the war, then, at first, it was called the crusades and Jihad: today nothing has changed. The 21 st century opened with the bombing of the World Trade Centre buildings in New York, US by Arabs and Muslims a la George Bush Jnr., President of the United Stated of Africa in a post attack briefings of the joint session of congress. Bush thereafter vowed that the world was not going to be the same again. That outburst marked the declaration of the war against terror which claimed the independence and sovereignty of first the Afghans, Iraqis, Somalis and is now threatening the Iranians (Persians), Syrians, and anybody who is caught in the crossfire.